Patient-centered perspectives: A qualitative evaluation of the Hip Instructional Prehabilitation Program for Enhanced Recovery (HIPPER) - Aditya Dhariwal; Somayyeh Mohammadi; Ethan Simpson; Marie D. Westby; Wendy Watson; William C. Miller (PLoS ONE, 2025)
Over 55,000 total hip replacement (THR) surgeries were performed in Canada in 2021, with the number rising each year. Excluding rehabilitation, the cost of hip replacement procedures exceeded $675 million, a large burden on the Canadian healthcare system. Considering this large financial impact, prehabilitation delivered through electronic health (eHealth) can improve post-surgical outcomes and reduce overall healthcare expenditures by enhancing recovery and reducing hospital length of stay. This study utilized grounded theory to examine user experience of the Hip Instructional Prehabilitation Program for Enhanced Recovery (HIPPER), an eHealth approach to prehabilitation education. Participants were purposively sampled and conventional content analysis was conducted on 18 transcribed semi-structured interviews with participants who completed the HIPPER program in preparation for THR surgery. We identified three categories and seven subcategories: 1) ‘That wasn’t so hard!’, with the subcategories easy to use, learning information and appreciating HIPPER, which describe how participants were able to learn information and use the modules easily; 2) ‘I’m ready’, comprising of the subcategories being prepared for surgery and having a smooth and good experience which relates to how participants were prepared and confident going into surgery; 3) ‘I’d like to have seen’, including the subcategories having differing experiences and suggesting additions, which explore participants’ constructive criticism and ideas for improvement. Our results show useful features to include in eHealth programs and demonstrate how educational prehabilitation in the form of eHealth is helpful and usable for older adults undergoing THR. We also discuss and inform the integration of feedback and development of eHealth programs for elective surgical procedures. This study was registered with ClinicalTrials.gov on November 21, 2016 with the registration number NCT02969512.